IMPROVING STUDENTS’ SPEAKING SKILL USING TEAM ASSISTED INDIVIDUALIZATION (TAI) TO THE SECOND YEAR STUDENTS OF SMP NEGERI 2 GROGOL IN 2010/2011 ACADEMIC YEAR (A CLASSROOM ACTION RESEARCH) - ASTUTI, ALFIA AYU (2011)
This study in implementing Team Assisted Individualization, describes whether Team Assisted Individualization can increase the students’ speaking skill. The study was done in SMP N 2 Grogol at the second year, using action research. The researcher took 34 students as the subject of the research. The researcher taught speaking English using Team Assisted Individualization method. The action consisted of two cycles in which each cycle consists of two meetings, and each cycle consists of four elements, namely: planning, implementing, observing, and reflecting. To collect the data the researcher used observation, interview, and documents that consisted of tests (pre-test and posttest), and lesson plan. The result of the research shows that, by implementing Team Assisted Individualization in teaching speaking, the students have chance to be active and cooperative in teaching speaking. The students motivate themselves to speak and to practice speaking and the students’ speaking achievement is better. It can be seen from the result of the students’ activities during action, and the students speaking achievement of speaking. The result of pre-test score shows that there are 12 students who got score at scale (0-40), 8 students who got score at scale (41-55), and 14 students who got score at scale (56-70). While the result of posttest score shows that there are 4 students who got score at scale (41-55), 21 students who got score at scale (56-70), 9 students who got score at scale (71-85). From the students’ responses, it is found that most of the students said that they like this technique. They could easily learn English speaking. The students admitted that their speaking skill is improved. The students could do post-test better than pre-test which means that the teaching speaking using Team Assisted Individualization is successful to improve the students’ motivation to speak.